ANALISA BISNIS PENGOLAHAN SAMPAH MENJADI BAHAN BAKAR RDF BERBASIS WAKAF PRODUKTIF DI KOTA BOGOR - Jatmiko, Sigit Wahyu; Chaniago, Asdi; Misno (Institut Agama Islam Sahid Bogor, 2024)
The aim of this research is to analyze the feasibility of processing waste into fuel, by utilizing productive waqf financing. The research was carried out by collecting data from literature studies and field surveys at the Galuga Bogor TPA, and analyzing it descriptively qualitatively and quantitatively technically and economically. In the financial aspect, it shows the value: NPV IDR 1,660,445,113.55; IRR 17.78 percent; B/C Ratio 1.10 and PBP 4.52 years. The variable cost component, RDF sales price and tipping fee income shows a value of 4.31; 6.70 ; 2.25, this value shows that it is sensitive to change. As a corporate entity that receives tipping fees from the government by involving funding from waqf, this is very feasible, both in part and in total investment costs. Seeing the small level of risk, waqf funds can be used for the RDF production business with a Mudhorobah or Musyarokah pattern, the whole capital or part of it, with sharia principles), with a period of 10-25 years